Relationship Between Precision of Standard Implementation Operational Installation Procedure With Signs of Phlebitisin Hospital ICU X - Linda inayati; Achmad Dafir Firdaus; Risna Yekti M (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2022)
Phlebitis is an inflammation of the veins caused by the act of administering intravenous therapy by nurses while the patient is in hospital. the incidence of phlebitis can also be influenced by the knowledge of the nurse providing care. Standard Operating Procedures (SPO) are intended to eliminate doubts and serve as guidelines for nurses when carrying out activities that must be adjusted to institutional policies and standards, and must be updated whenever necessary. The purpose of this study was to determine the relationship between the accuracy of the SOP for infusion and signs of phlebitis. The research design was observational with a cross sectional approach. Sampling using purposive sampling with a sample size of 67 respondents to patients and 20 samples of respondents to nurses. Correlation test using Spearmen Rho. This study showed a crosstab of 19.4% of respondents showed signs of phlebitis if the SOP for infusion was done incorrectly and if the SOP for infusion was carried out correctly, 52.2% of the respondents did not have any signs of phlebitis. The results showed that the Spearmen Rho correlation test obtained p = 0.000 or p> 0.05, then H1 was accepted, with a 95% confidence level, it could be concluded that the accuracy of the implementation of the SOP for infusion was associated with signs of phlebitis. The value of the correlation coefficient (r) shows a negative sign with a value of -0.546, which means that the accuracy of the SOP for infusion is inversely proportional to the signs of phlebitis.